Depression and the meaning of life in university students in times of pandemic - Romero Parra, Mireya (2020)
The emergence of the pandemic has led to fundamental social and economic swaps throughout the world, the sponsored measures taken have a significant effect on the mental health of individuals. The objective of the study was to compare the level of depression related to the meaning of life in students in times of pandemic at the Continental University of Peru and the "Rafael María Baralt" National Experimental University of Venezuela. The type of research developed was descriptive correlational with a cross-sectional design. The sample was made up of two groups: the first corresponds to 300 students from Peru and 300 from Venezuela. The Beck Depression Inventory and the Dimensional Sense of Life Scale, standardized version for Latin America, were used as measurement instruments. With the Spearman correlation coefficient it was determined that there is a moderate negative relationship of -.610, which indicates that there is an inverse correlation in the variables level of depression and sense of life of the students and it was concluded that, among the students university students from both countries, there is a moderate inverse significant correlation between depression and the meaning of life, in the current times of pandemic.